Tour Guide Competence in Gastronomy Tours - Abdullah Ülkü; Levent Selman Göktaş (Journal of Tourismology)
This qualitative study investigates the competence of gastronomy tour guides using content analysis. Semi-structured interviews were conducted between 14 and 20 December 2021 with 20 professional tour guides with at least 8 years’ experience who conduct gastronomy tours in Gaziantep, Türkiye. The following 14 themes emerged from the content analysis: level of knowledge, audio-visual media, cultural predisposition, occupational competence, specialization, culture, education/training, knowledge of products, knowledge of places for food and beverages, problem-solving skills, communication, ability to empathize, recipes, and culinary culture. The findings revealed that tour guides should know about the gastronomic elements that they present and the connection of these elements with the region’s cultural and social structure. The tour guides’ presentations are not well-structured in terms of the comprehensiveness of the information presented and their choice of words. Gastronomic tour guides should therefore acquire information from reliable sources and learn more about tourist psychology, tourism sociology, personal development, and communication skills, including effective and eloquent speaking.